The Effects of Academic Advising on Juniors and Seniors of English Department at Balkh University - Zewary, Sayed Mustafa (European Journal of Social Science Education and Research, 2024)
Academic advising is the process between the students and academic advisors who exploring the value of a general education, reviewing the services and policies of the institution, discussing educational and career plans to make appropriate course selection goals for their students. Some studies have been conducted on academic advising and its effects on students’ academic development. Therefore, the present paper is an attempt to contribute the previous studies by presenting the factors that academic advising has an impact on students’ academic development. Thus, this paper will explore whether academic advising is efficient to the students or not. For this purpose, previous studies were reviewed, and the questionnaire was shaped. The participants were selected randomly who are the juniors and seniors (61% females and 39% males) of English Department at Balkh University. In the long run, the analysed data revealed that the functions of academic advising have impact on students’, success, development, educational outcomes, students’ satisfactions and students’ retention.
Keywords: academic success, academic development, educational outcome, student’s satisfactions and speculative retention